Chewing Lice (Insecta: Phthiraptera) on Mallards (Anas platyrynchos) in Turkey - Aksin, Nursel (Medwell Online, 2011)
This research was conducted to determine species of chewing lice (Phithiraptera) on mallard (Anus platyrynchos). For this purpose, twelve mallards (Anseriformes: Anatidae), obtained in different areas of Elazig province (Eastern Anatolian region) of Turkey from 2004 and 2006, during. the hunting season between October to February were examined in terms of chewing lice. Three different chewing lice species were found on the infested mallards. These species were identified as Anaticola crassicornis (Scopoli, 1763), Trinoton querquedulae (Linnaenus, 1758) and Anatoecus sp. (nymph). In this study, the evidence of A. crassicornis, T. querquedulae and Anatoecus sp., on mallards is reported for the 1st time in Turkey.
Keywords: Chewing lice; mallards; Anaticola crassicornis; Trinoton querquedulae; Anatoecus sp.; Turkey